2002
DOI: 10.1152/ajpgi.00189.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by which endogenous glucocorticoid protects against indomethacin-induced gastric injury in rats

Abstract: . Mechanisms by which endogenous glucocorticoid protects against indomethacin-induced gastric injury in rats. Am J Physiol Gastrointest Liver Physiol 283: G1082-G1089, 2002. First published July 31, 2002 10.1152/ajpgi.00189.2002We investigated the mechanisms underlying the protective action of glucocorticoids against indomethacin-induced gastric lesions. One-week adrenalectomized rats with or without corticosterone replacement (4 mg/kg sc) were administered indomethacin (25 mg/kg sc), and gastric secretion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 45 publications
6
38
0
2
Order By: Relevance
“…Fasting is a required component of gastric ulcerogenic models (Kato et al 2009;Rios et al 2010;Zelena and Filaretova 2010). Beside GI components our previous results have already shown that a general reduction in blood glucose induced by IM injection (Filaretova et al 2002) is a key element in the pathogenesis of the injury triggering an increase in gastric motility (Laine et al 2008;Hermann et al 2014). The results of 24 h telemetric recordings show circadian variation of heart rate, core body temperature, and locomotion with higher levels during the dark phase and lower levels during the light phase in control rats.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Fasting is a required component of gastric ulcerogenic models (Kato et al 2009;Rios et al 2010;Zelena and Filaretova 2010). Beside GI components our previous results have already shown that a general reduction in blood glucose induced by IM injection (Filaretova et al 2002) is a key element in the pathogenesis of the injury triggering an increase in gastric motility (Laine et al 2008;Hermann et al 2014). The results of 24 h telemetric recordings show circadian variation of heart rate, core body temperature, and locomotion with higher levels during the dark phase and lower levels during the light phase in control rats.…”
Section: Discussionmentioning
confidence: 92%
“…To continue our strategy of using integrative approach ( Filaretova et al 2002;Filaretova et al 2006;Filaretova et al 2009;Filaretova 2011;Filaretova et al 2014) and to understand what happens with the body as a whole ("in vivo"), in the present study we evaluated somatic and behavior changes in rats treated with IM at gastric ulcerogenic dose. Additionally to an appearance of severe injury to the small intestine, body and thymus weights were reduced while adrenal weight and the morning plasma corticosterone levels were enhanced 3 days after IM injection (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-inflammatory properties of glucocorticoids may also contribute to their gastroprotective action. Glucocorticoids as antiinflammatory hormones may contribute to gastroprotection by inhibition of neutrophil adherence (Wallace, 1997) and attenuation of microvascular permeability (Filaretova et al, 2002c). Because the glucocorticoid receptors are expressed ubiquitously it is possible that glucocorticoids may act directly on local gastric targets as well as using a more general mechanism.…”
Section: 3mentioning
confidence: 99%
“…Insufficient supply of glucose may stimulate hypothalamic glucose-sensitive neurons (Mobbs et al, 2001, as cited in Filaretova et al, 2002c), resulting in a vagally-mediated increase in gastric motility and secretion (Shiraishi, 1988, as cited in Filaretova et al, 2002c) that are well-known pathogenic elements in various gastric ulcerogenic models. Exogenous glucose reverses the hypoglycemia-induced stimulation of hypothalamic glucose-sensitive neurons (Oomura et al, 1974, as cited in Filaretova et al, 2002c), inhibits vagally-mediated gastric hypermotility (Barnett & Owyang, 1988, as cited in Filaretova et al, 2002c) and attenuates gastric ulceration (Takeuchi et al, 1990, as cited in Filaretova et al, 2002c). It was reasonable to assume that the maintenance of glucose homeostasis by glucocorticoid hormones could be fundamental to their beneficial actions on local gastric targets.…”
Section: 3mentioning
confidence: 99%